2001
DOI: 10.1080/00034980120094730
|View full text |Cite
|
Sign up to set email alerts
|

Human cystic echinococcosis: contributions to the natural history of the disease

Abstract: In areas where human cystic echinococcosis (CE) is endemic, the results of ultrasonographic or X-ray examinations have revealed a surprisingly high prevalence of abdominal cysts in asymptomatic individuals. The results of preliminary studies indicate that the ratio of liver infection:lung infection (LI:LU) is much higher in the asymptomatic individuals (9:1 or 7:1) than is usual among symptomatic cases of liver CE (2:1). This difference may indicate that, compared with lung cysts, liver cysts rarely cause morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 21 publications
4
32
2
6
Order By: Relevance
“…The induction of morbidity depends on the number, size, and developmental status of the cyst(s) (active or inactive), the involved organ, the localization of the cyst(s) within the organ, the pressure of cysts on surrounding tissues and structures, and the defense mechanisms of the infected individual. Ultrasonographic studies in South America have shown that the average diameter of cysts in asymptomatic carriers was significantly smaller (approximately 4 cm) than that in symptomatic patients (approximately 10 cm) (126). According to Perdomo et al (151), approximately 88% of cysts detectable in asymptomatic carriers were Ͻ7.5 cm in diameter.…”
Section: Vol 17 2004 Biology and Epidemiology Of Echinococcosis 109mentioning
confidence: 99%
See 2 more Smart Citations
“…The induction of morbidity depends on the number, size, and developmental status of the cyst(s) (active or inactive), the involved organ, the localization of the cyst(s) within the organ, the pressure of cysts on surrounding tissues and structures, and the defense mechanisms of the infected individual. Ultrasonographic studies in South America have shown that the average diameter of cysts in asymptomatic carriers was significantly smaller (approximately 4 cm) than that in symptomatic patients (approximately 10 cm) (126). According to Perdomo et al (151), approximately 88% of cysts detectable in asymptomatic carriers were Ͻ7.5 cm in diameter.…”
Section: Vol 17 2004 Biology and Epidemiology Of Echinococcosis 109mentioning
confidence: 99%
“…A different situation exists in infected but asymptomatic individuals. Ultrasonographic and chest X-ray surveys of approximately 10,000 apparently healthy individuals living in areas of Argentina and Uruguay with endemic infection revealed liver-to-lung ratios of 6:1 and 12:1, respectively (126). An explantation for the shift from the higher liver-to-lung ratios in asymptomatic individuals to lower values (2.5:1) in hospitalized patients is that lung cysts cause more frequently morbidity than hepatic cysts (126).…”
Section: Vol 17 2004 Biology and Epidemiology Of Echinococcosis 109mentioning
confidence: 99%
See 1 more Smart Citation
“…29 The resulting value was subsequently adjusted to account for the fact that abdominal ultrasound is unable to detect pulmonary cases, which have represented 11-13.5% of all undiagnosed cases in other studies. 30,31 This adjustment resulted in an estimated CE prevalence of 2.07%, the maximum value in the uniform distribution used to estimate the prevalence of undiagnosed CE in Rio Negro Province.…”
Section: Study Area Rio Negro Province Is Located In the Northernmentioning
confidence: 99%
“…[4][5][6] Although the growth rate of echinococcal cysts is extremely variable, it basically depends on the organ compliance, reaching larger sizes in the lungs and growing at slower pace in the liver, spleen, or kidneys. 17 If a cyst does not become complicated (infected or ruptured), symptoms related to the enlargement of the cyst only appear several years after the infection. Not infrequently, the diagnosis is incidentally established when a patient is evaluated for other diseases.…”
Section: Discussionmentioning
confidence: 99%